Label-free capacitive assaying of biomarkers for molecular diagnostics - Garrote, Beatriz L. [UNESP]; Santos, Adriano [UNESP]; Bueno, Paulo R. [UNESP] (Springer Nature, 2020)
The label-free analysis of biomarkers offers important advantages in developing point-of-care (PoC) biosensors. In contrast to label-based methodologies, such as ELISA, label-free analysis enables direct detection of targets without additional steps and labeled reagents. Nonetheless, label-free approaches require high sensitivity to detect the intrinsic features of a biomarker and low levels of nonspecific signals. Electrochemical capacitance, Cμ¯, is a feature of electroactive nanoscale films that can be measured using electrochemical impedance spectroscopy. Cμ¯ is promising as an electrochemical transducing signal for the development of high-sensitivity, reagentless and label-free molecular diagnostic assays. We used a proprietary ferrocene (Fc)-tagged peptide that is able to self-assemble onto gold electrodes (thicknesses <2 nm) to which any biological receptor can be coupled. When coupled with biological receptors (e.g., a monoclonal antibody), Cμ¯ exhibited by the redox-tagged peptide changes as a function of the target concentration. We provide herein the steps for the qualitative and quantitative detection of dengue non-structural protein 1 (NS1) biomarker. Detection of NS1 can be used to diagnose dengue virus infection, which causes epidemics each year in tropical and subtropical regions of the world. Including the pre-treatment of the electrode surface, the analysis takes ~25 h. This time can be reduced to minutes if the electrode surface is fabricated separately, demonstrating that Cμ¯ is promising for PoC applications. We hope this protocol will serve as a reference point for researchers and companies that intend to further develop capacitive devices for molecular diagnostic assays.